SPIRITUAL ENHANCEMENT THROUGH PRENATAL GENTLE YOGA WITHIN ISLAMIC CULTURAL CONTEXTS - Machmudah, Anisah; Rahmat, Munawar; Kosasih, Aceng; Azka, Ibnu; Hamrain, Fathur Baldan (Al-Qalam, 2024)
Prenatal education is an important aspect in preparing pregnant women holistically to face the process of pregnancy and childbirth. This study aims to examine the integration of gentle yoga with Islamic spiritual values as an approach in Islamic prenatal education. Gentle yoga, with a focus on gentle physical exercise, breathing techniques, meditation, and relaxation, offers various benefits for the physical and emotional health of pregnant women. On the other hand, Islamic spiritual values emphasize the importance of maintaining physical and mental health and getting closer to Allah SWT. This study used a qualitative method with a literature study approach and in-depth interviews with pregnant women and Islamic scholars. Data were analyzed to understand the views and practices related to the integration of gentle yoga and spiritual education in the context of pregnancy. The results showed that gentle yoga integrated with Islamic spiritual values can improve the physical, emotional, and spiritual well-being of pregnant women. This practice helps pregnant women feel calm, patient, and close to Allah SWT, as well as strengthen gratitude and inner peace. The conclusion of this study confirms that Islamic prenatal education that combines gentle yoga and Islamic spiritual values offers an effective holistic approach to preparing pregnant women. The implementation of such prenatal education can provide comprehensive support for pregnant women, both physically, mentally, and spiritually. This study provides a significant contribution to the development of a prenatal education approach that is in accordance with Islamic teachings and beneficial for the health of pregnant women.